2022
DOI: 10.1186/s12880-022-00806-5
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy and influencing factors of Doppler echocardiography in estimating pulmonary artery systolic pressure: comparison with right heart catheterization: a retrospective cross-sectional study

Abstract: Background Noninvasive assessment of pulmonary artery systolic pressure by Doppler echocardiography (sPAPECHO) has been widely adopted to screen for pulmonary hypertension (PH), but there is still a high proportion of overestimation or underestimation of sPAPECHO. We therefore aimed to explore the accuracy and influencing factors of sPAPECHO with right heart catheterization (RHC) as a reference. Methods A total of 218 highly suspected PH patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…In our previous study [ 2 ], Bland–Altman analysis demonstrated low bias between RHC and TR-derived parameters with wide limits of agreements. In our patients, TR-sPAP ECHO in Moderate TR group had the greatest correlation coefficient with mPAP RHC (0.742, p < 0.001) followed by Mild TR group (0.635, p < 0.001) and severe group (0.592, p = 0.033).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous study [ 2 ], Bland–Altman analysis demonstrated low bias between RHC and TR-derived parameters with wide limits of agreements. In our patients, TR-sPAP ECHO in Moderate TR group had the greatest correlation coefficient with mPAP RHC (0.742, p < 0.001) followed by Mild TR group (0.635, p < 0.001) and severe group (0.592, p = 0.033).…”
Section: Resultsmentioning
confidence: 97%
“…Peak velocity of TR (TR Vmax) and its derived parameters systolic and mean pulmonary artery pressure (PAP) by Doppler echocardiography (sPAP ECHO and mPAP ECHO ) are most commonly used for assessing PH. We previously investigated the accuracy and impact factors of TR in estimating PAP and have demonstrated sPAP ECHO was superior than other TR-related methods in screening PH [ 2 ]. However, in precapillary PH, the true incidence of TR and the distribution of different TR degree are still poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been a number of earlier studies that indicate that echocardiographic estimates of PA pressure are frequently inaccurate 6,7 . The estimated error ranged from −20 to +25 mmHg compared to data from RHC 8–10 . This was mainly contributed to the morphological variation of reflux flow and reflux caliber, and right ventricular volume load and systolic function, intra‐ and interexaminer variability, and other factors 11 .…”
Section: Introductionmentioning
confidence: 98%
“…6,7 The estimated error ranged from −20 to +25 mmHg compared to data from RHC. [8][9][10] This was mainly contributed to the morphological variation of reflux flow and reflux caliber, and right ventricular volume load and systolic function, intra-and interexaminer variability, and other factors. 11 On the other hand, using the estimated pressure alone is not sufficient to diagnose PH.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Compared to RHC, echocardiography has been shown to be a reliable method in several studies. 10 , 11 In the 2015 European Society of Cardiology (ESC)/European Respiratory Society (ERS) Guidelines for the Diagnosis and Treatment of Pulmonary Hypertension, echocardiography is the preferred non-invasive test for PH screening and follow-up; the guidelines also recommend that it should be used to screen for PH in patients whose clinical data suggest an increased risk of PH. 12…”
Section: Introductionmentioning
confidence: 99%